Assessment of the impacts of rapid Marine Heatwaves and cumulative thermal stress on cold-water upwelling coral refugia - Po-Chun Hsu; Rose Angeli Tabanao Macagga; Roshin P. Raj (Geomatics, Natural Hazards & Risk)
This study introduces a combined Marine Heatwaves-Degree Heating Weeks (MHW-DHW) analysis to evaluate climate change impacts on three coral refugia: Green Island, Nanwan Bay, and Dongsha Atoll. MHWs reflect rapid rises in Sea Surface Temperature (SST) and their timing, while DHW captures sustained high SSTs, indicating thermal stress, potential bleaching risks, and vulnerability of coral habitats. Since 2016, rapid MHW development has significantly increased annual thermal stress. Between 2020 and 2022, nearly half of each year they faced MHW threats corresponding to Bleaching Alert Levels 2 and 3. Historically, bleaching events were linked to strong El Niño transitioning to strong La Niña conditions during the negative phase of the Pacific Decadal Oscillation; however, recent sustained global ocean warming has masked this pattern. Periodic cooling due to upwelling in these habitats is not fully captured by the CoralTemp dataset due to smoothing and low spatial resolution. CoralTemp SST values differ from Himawari satellite observations by about 1 to 1.4 °C in daily minima, leading to average SST discrepancies of 0.2–0.5 °C. This suggests diurnal temperature variations may still mitigate sustained high temperatures. Furthermore, multi-satellite data revealed that rapid MHW development has not significantly affected chlorophyll concentrations within coral habitats.